A partitioned gradient composite material battery shell and preparation method thereof
Patent Information
- Application Number
- CN202210658451.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-06-12
AI Technical Summary
当电池外壳受到外界强大的冲击力时,会造成内部电池芯急剧变形或者温度急剧升高,在高温环境下,电池箱体易发生软化,变形,最后可能发生破裂、燃烧、爆炸,燃烧产生的有害气体对人们身体损害极大
Smart Images

Figure CN114976398B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a partitioned gradient composite material battery shell, belonging to the technical field of battery application. Background Art
[0002] New energy vehicles have driven green development, and the mileage of electric vehicles has received widespread attention. In order to alleviate mileage anxiety, people undoubtedly need safe, lightweight and cost-effective electric vehicles. In order for electric vehicles to achieve this goal in the market, their components must also have these qualities. If the battery housing can be made of lighter materials, and the safety and functionality are greatly improved due to its special structure and material properties, then it is undoubtedly a wise choice for designers and material screeners of original equipment manufacturers and system suppliers. Therefore, the preparation and configuration design of a partitioned gradient composite battery housing is very urgent to overcome.
[0003] When an electric vehicle battery is overcharged, short-circuited, abused, or other abnormal conditions occur, it may cause the battery to overheat, causing the battery casing to burn and causing extreme situations such as vehicle spontaneous combustion and explosion. When the battery casing is subjected to a strong external impact, the internal battery core will be deformed sharply or the temperature will rise sharply. In a high temperature environment, the battery casing is prone to softening and deformation, and may eventually rupture, burn, and explode. The harmful gases produced by the combustion are extremely harmful to people's bodies. Among the existing technologies, most of them apply fireproof materials to the interlayer of the electric vehicle battery casing or apply fireproof coatings to the inside of the battery casing to achieve a simple fireproof function. When subjected to external force impact, the simple fireproof device plays a very small role and is easy to fall off, and the effect of reducing combustion is ultimately very small. The above methods not only increase the weight and cost of the battery casing, but also fail to improve the strength of the battery casing. Summary of the invention
[0004] The object of the present invention is to provide a partitioned gradient composite material battery shell, which has the characteristics of high strength, impact resistance and good thermal conductivity. The battery shell includes a hardness zone material layer, a transition zone material layer and a heat dissipation zone material layer from the outside to the inside. The transition zone material layer serves as the core layer of the battery box, and its shape is a multiple honeycomb;
[0005] The transition area material layer is arranged between the hardness area material layer and the heat dissipation area material layer.
[0006] Preferably, the thickness ratio of the hardness zone material layer, the middle honeycomb material layer, and the heat dissipation zone material layer of the present invention is 1:2:1.
[0007] Preferably, the hardness zone material layer, transition zone material layer and heat dissipation zone material layer of the present invention are integrated into a whole through gradient 3D printing.
[0008] Another object of the present invention is to provide a method for preparing the zoned gradient composite material battery housing, which specifically comprises the following steps:
[0009] (1) Using modeling software to build a three-dimensional model of the battery case and convert the model into two-dimensional slices recognized by the printer, and select different areas for 3D printing;
[0010] (2) The material layer of the hardness zone is Al-Zn-Mg alloy. Specifically, Al powder is placed in the No. 1 powder spray box, Zn powder is placed in the No. 2 powder spray box, and Mg powder is placed in the No. 3 powder spray box; the corresponding outer shell selection area is selected to print the material layer of the hardness zone;
[0011] (3) The material layer of the transition zone is Al-Fe-Si alloy. Specifically, Al powder is placed in the No. 1 powder spray box, Si powder is placed in the No. 2 powder spray box and stirred thoroughly; Fe powder is placed in the No. 3 powder spray box; the corresponding transition zone honeycomb is selected to print the transition zone material layer;
[0012] (4) The material layer of the heat dissipation area is Al-Si-Mg alloy. Specifically, put Al powder into the No. 1 powder spray box; put Si powder into the No. 2 powder spray box and stir it thoroughly; put Mg powder into the No. 3 powder spray box; select the corresponding area to print the heat dissipation area material layer.
[0013] Preferably, the mass percentages of element powders in the Al-Zn-Mg alloy in step (2) of the present invention are: Mg powder 1.4-9%; Zn powder 4.5-12%; and the balance is Al powder.
[0014] Preferably, the mass percentages of the element powders in the Al-Fe-Si alloy in step (3) of the present invention are: Si powder 1-2%; Fe powder 1-2%; and the remainder is Al powder.
[0015] Preferably, the mass percentages of the element powders in the Al-Si-Mg alloy in step (4) of the present invention are: Si powder 1-2%; Mg powder 0.1-0.2%; and the balance is Al powder.
[0016] Beneficial effects of the present invention:
[0017] (1) The method of the present invention forms the hardness zone material layer, the transition zone material layer, and the heat dissipation zone material layer into an integral structure through gradient 3D printing, and the middle honeycomb layer plays a role in buffering the impact force, thereby avoiding the problem of the fireproof isolation layer being broken or the surface coating falling off due to external force impact; the battery shell after molding has the characteristics of high strength, fast thermal conductivity, impact resistance, and light weight, thereby improving the safety and reliability of the battery shell; it has mechanical properties that ordinary battery shells cannot achieve, so that the life of the battery shell can be qualitatively improved under certain conditions.
[0018] (2) The raw materials required by the present invention are cheap and widely available, and materials of different shapes and gradients can be printed out later as required. The required equipment is simple, easy to operate, and suitable for large-scale batch production. The preparation of three-dimensional modeling is simple, the processing process is safe, and a variety of powders are used in the preparation process for real-time uniform mixing, which can replace the cumbersome, high-cost, and inaccurate work of workers, and realize advanced three-dimensional printing. Different powder feeding rates are accurately controlled during the preparation process, and uniform melting is performed under the high temperature state of the laser. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic diagram of the structure of the stepped partition gradient composite material battery housing of the present invention;
[0020] Figure 2 It is a schematic diagram of the structure of the transition layer of the battery shell of the zoned gradient composite material of the present invention. DETAILED DESCRIPTION
[0021] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the contents described above.
[0022] The 3D printing system of the present invention is composed of a laser, a six-axis control center, a multi-channel powder feeding device, an inert gas protection box, and a multi-axis powder feeding head. The base plate material is 45 steel, with a size of 50mm*50mm*10mm; the powder feeding amount is continuously adjustable in the range of 0-40g / min, the maximum powder feeding amount is 40g / min, and the applicable range of additive powder particle size is 60-150μm; the laser output power range is 50-3000W; the spot diameter range is Φ1-Φ2.5mm and can be changed; the focal length of the focusing mirror is about 119mm.
[0023] Example 1
[0024] The gradient component gear described in this example is divided into three working areas from the outside to the inside, namely, the hardness zone material layer, the transition zone material layer, and the heat dissipation zone material layer; the thickness ratio of the three working areas, the hardness zone material layer, the transition zone material layer, and the heat dissipation zone material layer is 1:2:1; the three-dimensional model of the gear is established using modeling software and the modeling is converted into a two-dimensional slice recognized by the printer, different areas are selected for 3D printing, and different areas are configured with different metal powder contents.
[0025] Hardness zone material layer: the mass percentages of Al-Zn-Mg alloy element powder are: Mg powder 9%; Zn powder 8%; and the balance is Al powder.
[0026] Transition zone material layer: the mass percentages of Al-Fe-Si alloy element powder are: Si powder 1.5%; Fe powder 1%; the balance is Al powder.
[0027] Heat dissipation zone material layer: the mass percentage of Al-Si-Mg alloy element powder is: Si powder 2%; Mg powder 0.1%; the balance is Al powder.
[0028] Configure printer parameters: Powder beam diameter within 30mm after the outlet: Φ1-Φ5mm; powder feeding amount is continuously adjustable, ranging from 0-40g / min, maximum powder feeding amount is 40g / min, and the applicable range of powder particle size is 60-150μm; laser output power range is 50-3000W; spot diameter variation range is Φ1-Φ2.5mm and can be changed; focusing mirror focal length is about 119mm; the host computer synchronously transmits scanning path data to the robot online, and the robot executes the transmission path data online in real time; protective atmosphere environment is used for protection, and the precision error of the powder spreading device is strictly controlled according to the process requirements to evenly spray powder in the molding box, and the laser temperature is strictly controlled for selected area printing. After completing one selected area, the next selected area is printed. In this way, three selected area printings are performed to complete the printing of the entire selected area gradient battery shell.
[0029] Post-processing: Send the printed battery shell into a vacuum chamber with a vacuum degree of 10 -2 ~10 -4 The heat treatment was carried out in the heat treatment chamber of Pa, and the temperature was kept at 880℃ for 2.5 hours. After cooling to room temperature in the furnace, the gradient gear after heat treatment was sandblasted and polished to the required accuracy according to the process requirements.
[0030] Example 2
[0031] The gradient component gear described in this example is divided into three working areas from the outside to the inside, namely, the hardness zone material layer, the transition zone material layer, and the heat dissipation zone material layer; the thickness ratio of the three working areas, the hardness zone material layer, the transition zone material layer, and the heat dissipation zone material layer is 1:2:1; the three-dimensional model of the gear is established using modeling software and the modeling is converted into a two-dimensional slice recognized by the printer, different areas are selected for 3D printing, and different areas are configured with different metal powder contents.
[0032] Hardness zone material layer: the mass percentages of Al-Zn-Mg alloy element powder are: Mg powder 1.4%; Zn powder 12%; and the balance is Al powder.
[0033] Transition zone material layer: the mass percentages of Al-Fe-Si alloy element powder are: Si powder 2%; Fe powder 1.5%; the balance is Al powder.
[0034] Heat dissipation zone material layer: the mass percentage of Al-Si-Mg alloy element powder is: Si powder 1.5%; Mg powder 0.15%; the balance is Al powder.
[0035] Configure printer parameters: Powder beam diameter within 30mm after the outlet: Φ1-Φ5mm; powder feeding amount is continuously adjustable, ranging from 0-40g / min, maximum powder feeding amount is 40g / min, and the applicable range of powder particle size is 60-150μm; laser output power range is 50-3000W; spot diameter variation range is Φ1-Φ2.5mm and can be changed; focusing mirror focal length is about 119mm; the host computer synchronously transmits scanning path data to the robot online, and the robot executes the transmission path data online in real time; protective atmosphere environment is used for protection, and the precision error of the powder spreading device is strictly controlled according to the process requirements to evenly spray powder in the molding box, and the laser temperature is strictly controlled for selected area printing. After completing one selected area, the next selected area is printed. In this way, three selected area printings are performed to complete the printing of the entire selected area gradient battery shell.
[0036] Post-processing: Send the printed battery shell into a vacuum chamber with a vacuum degree of 10 -2 ~10 -4 The heat treatment was carried out in the heat treatment chamber of Pa, and the temperature was kept at 880℃ for 2.5 hours. After cooling to room temperature in the furnace, the gradient gear after heat treatment was sandblasted and polished to the required accuracy according to the process requirements.
[0037] Example 3
[0038] The gradient component gear described in this example is divided into three working areas from the outside to the inside, namely, the hardness zone material layer, the transition zone material layer, and the heat dissipation zone material layer; the thickness ratio of the three working areas, the hardness zone material layer, the transition zone material layer, and the heat dissipation zone material layer is 1:2:1; the three-dimensional model of the gear is established using modeling software and the modeling is converted into a two-dimensional slice recognized by the printer, different areas are selected for 3D printing, and different areas are configured with different metal powder contents.
[0039] Hardness zone material layer: the mass percentage of Al-Zn-Mg alloy element powder is: Mg powder 5%; Zn powder 4.5%; the balance is Al powder.
[0040] Transition zone material layer: the mass percentage of Al-Fe-Si alloy element powder is: Si powder 1%; Fe powder 2%; the balance is Al powder.
[0041] Heat dissipation zone material layer: the mass percentage of Al-Si-Mg alloy element powder is: Si powder 1%; Mg powder 0.2%; the balance is Al powder.
[0042] Configure printer parameters: Powder beam diameter within 30mm after the outlet: Φ1-Φ5mm; powder feeding amount is continuously adjustable, ranging from 0-40g / min, maximum powder feeding amount is 40g / min, and the applicable range of powder particle size is 60-150μm; laser output power range is 50-3000W; spot diameter variation range is Φ1-Φ2.5mm and can be changed; focusing mirror focal length is about 119mm; the host computer synchronously transmits scanning path data to the robot online, and the robot executes the transmission path data online in real time; protective atmosphere environment is used for protection, and the precision error of the powder spreading device is strictly controlled according to the process requirements to evenly spray powder in the molding box, and the laser temperature is strictly controlled for selected area printing. After completing one selected area, the next selected area is printed. In this way, three selected area printings are performed to complete the printing of the entire selected area gradient battery shell.
[0043] Post-processing: Send the printed battery shell into a vacuum chamber with a vacuum degree of 10 -2 ~10 -4 The heat treatment was carried out in the heat treatment chamber of Pa, and the temperature was kept at 880℃ for 2.5 hours. After cooling to room temperature in the furnace, the gradient gear after heat treatment was sandblasted and polished to the required accuracy according to the process requirements.
[0044] The results of Examples 1 to 3 are analyzed as follows:
[0045] At present, the curb weight of many long-range pure electric new energy vehicles has reached more than 2,000kg, far exceeding the weight of many traditional fuel vehicles, and a large part of the weight is mainly the battery pack. For example, the battery pack of the Tesla model 3 long-range version weighs 480kg, accounting for more than 30% of the curb weight; the aluminum-based lightweight battery shell of the present invention will reduce the mass by at least 20%; the battery shells of electric vehicles on the market are all ordinary steel Q345, with a yield limit of 345MPa and a strength limit of 490-675MPa. During the collision, the battery pack will crack and fall, causing secondary damage; the honeycomb middle layer of this product can greatly reduce the impact force, which is expected to reduce the impact force by 15%, and the final impact force on the battery core is only 416.5-573.75MPa.
[0046] The design life of ordinary electric vehicle batteries is 27 months. Most family cars are quite economical, and the batteries of new cars are often used for 3-4 years. The present invention uses a gradient composite material with a honeycomb structure as the middle layer, which greatly improves the service life of the battery core and can extend the service life by 10%. By consulting the literature, it can be seen that for a battery shell without a honeycomb core, the peak collision force is 232.8kN, while the peak collision force of a battery shell with a honeycomb core is 232.8kN. It can be seen that the peak collision force is increased by 9.5%. When impacted, the impact force will be greatly increased, the damage to the battery core will be greatly reduced, and its life will be greatly improved.
Claims
1. A method for preparing a zoned gradient composite material battery shell, characterized in that: The battery housing comprises, from outside to inside, a hardness zone material layer, a transition zone material layer, and a heat dissipation zone material layer, wherein the transition zone material layer serves as the core layer of the battery housing and has a multiple honeycomb shape; The transition area material layer is arranged between the hardness area material layer and the heat dissipation area material layer; The thickness ratio of the hardness zone material layer, the transition zone material layer, and the heat dissipation zone material layer is 1:2:1; The hardness zone material layer, the transition zone material layer and the heat dissipation zone material layer are integrated into a whole through gradient 3D printing; The method for preparing the zoned gradient composite material battery shell specifically comprises the following steps: (1) Use modeling software to build a three-dimensional model of the battery case and convert the model into two-dimensional slices that can be recognized by the printer, and select different areas for 3D printing; (2) The material layer of the hardness zone is Al-Zn-Mg alloy. Specifically, put Al powder into the No. 1 powder spray box, Zn powder into the No. 2 powder spray box, and Mg powder into the No. 3 powder spray box; select the corresponding outer shell selection area to print the hardness zone material layer; (3) The material layer of the transition zone is Al-Fe-Si alloy. Specifically, put Al powder into the No. 1 powder spray box, put Si powder into the No. 2 powder spray box and mix them thoroughly; put Fe powder into the No. 3 powder spray box; select the corresponding transition zone honeycomb to print the transition zone material layer; (4) The material layer of the heat dissipation area is Al-Si-Mg alloy. Specifically, put Al powder into the No. 1 powder spray box; put Si powder into the No. 2 powder spray box and stir it thoroughly; put Mg powder into the No. 3 powder spray box; select the corresponding area to print the heat dissipation area material layer; The mass percentages of the element powders in the Al-Zn-Mg alloy in step (2) are: Mg powder 1.4-9%; Zn powder 4.5-12%; the remainder is Al powder; The mass percentages of the element powders in the Al-Fe-Si alloy in step (3) are: Si powder 1-2%; Fe powder 1-2%; the remainder is Al powder; The mass percentages of the element powders in the Al-Si-Mg alloy in step (4) are: Si powder 1-2%; Mg powder 0.1-0.2%; and the remainder is Al powder.
Citation Information
Patent Citations
Safety protection power module
CN205752266U